Simulation Of Total Heat Loss From Wet Skin Surface Of Dairy Cattles - Chong, Yian Sia (Universiti Sains Malaysia, 2003)
In hot and humid environments, cows suffer from several heat stress that causes reduction in milk production and breeding inefficiencies. Generally, drops in milk yield of 20% to 30% following hot, muggy stretches are not uncommon in high producing herds without supplemental cooling. Therefore, the main purpose of this study is to develop a simulation model that simultaneously calculates heat and mass transfer from a wetted skin surface and fur layer of a cow. In addition, respiration and urine heat losses are also included in the model. The model predicts evaporative, convective, radiant, respiration and urine heat losses with respect to the changes of levels of skin wetness (25, 50 and 75%), air velocity (0.5, 1.0, 2.0 m/s), relative air humidity (20, 40, 80%), ambient air temperature (30, 35, 380C), breathing rate (40, 60, 80 breaths/min) and volume of urine discharged (0.5, 1.0, 1.5 l/h). In the model, fur layer (hair coat) properties such as fur thickness and hair density assumed are that of summer condition. This prediction is done through the numerical solution by using the commercial Matlab software with version 6.5. This project discussed in detail about the effect of the five parameters or factors (levels of skin wetness, air velocity, relative air humidity, ambient air temperature, breathing rate and volume of urine discharged) on the types of heat losses as mentioned above based on the predicted values obtained. Graphs and tables of results are generated to show the relationship between the heat losses and each parameter. Besides that, the suggestions and recommendation for the future work are also included in the end of the thesis.